Forward Contracting and the Welfare Effects of Mergers - Nathan H. Miller (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2013)
I extend the oligopoly model of Allaz and Vila (1993) to explore how forward contracting affects the adverse welfare consequences of horizontal mergers. I derive a welfare statistic that, within the context of the model, is free of structural parameters. The statistic allows for conclusions that generalize across different cost and demand conditions. I then show that exogenous forward contracting mitigates welfare loss but that endogenous forward contracting exacerbates welfare loss provided the relevant industry is sufficiently concentrated.
Keywords: 330